PENGARUH RETURN ON ASSET DAN RISK PROFILE TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Arthur Simanjuntak; Septony B. Siahaan; Rehulina Ibrena Br. Tarigan (Jurnal Ilmu Manajemen METHONOMIX, 2023)
This study aims to determine the effect of return on assets and risk profile on firm value with good corporate governance as a moderating variable in the agricultural sector listed on the Indonesian stock exchange for the 2017-2021 period. This research is a type of causal research. The data used in this study is secondary data which can be accessed through the websites www.idx.co.id and www.idnfinancials.com. The population of this study consisted of 24 companies. The sampling method used in this study was purposive sampling and a total of 13 sample companies were obtained for 5 observation periods (2017-2021) with a total of 65 research observations. The technique used in this study is Moderated Regression Analysis (MRA) using the SPSS 22 program. The results of this study indicate that ROA, BRISK have no effect on firm value partially. Meanwhile, GCG can influence significantly by strengthening the relationship between ROA and company value. GCG can also affect or be able to moderate BRISK's relationship to firm value.